EXAMINING THE EFFECTS OF AND MODERATING INFLUENCES ON ENVIRONMENTAL, SOCIAL AND GOVERNANCE INFORMATION DISCLOSURE ON VALUE-AT-RISK: EVIDENCE FROM CHINESE LISTED COMPANIES: ESG - Jing Wu; Chee Yoong Liew (International Journal of Business and Society, 2024)
Generally, research on the effects of Environmental, Social and Governance (ESG) information disclosure on listed companies is primarily limited to developed countries. By contrast, the current study is located in China and analyses whether ESG reduces the downside risk of listed companies in China, and whether political connections and institutional investors moderate this relationship. This study uses Chinese A-share listed companies from the Shanghai and Shenzhen stock markets from 2010 to 2021 as research samples. Results demonstrated that the inhibitory effect of enhancing ESG performance on enterprise risk is more significant in non-heavy polluting industries, non-state-owned enterprises, and enterprises in areas with low levels of marketisation. This study explores the economic implications of ESG performance from a Value-at-Risk (VaR) perspective, enriching the relevant research on ESG rating in China and providing a fresh perspective to better elucidate the economic significance of companies improving their ESG performance. This study introduces institutional investors and political connections as two moderating variables to analyse their effect on the relationship between ESG performance and VaR. In addition, heterogeneity analysis is carried out in combination with the industry, region, and ownership nature of listed companies to test the “insurance” and “information” effects of ESG performance, to provide decision-making references for investors, enterprise managers, and regulators.